Degree-Based Graph Invariants of some Chemical Structures for the Treatment of Corona Virus. (24th May 2022) - Amin, Shahid; Ali, Haidar; Rehman, M. A.; Mousa, Abd Allah A.; Andualem, Mulugeta
Abstract : Coronavirus is a family of viruses that cause upper respiratory infections in humans. It has several variants, e.g., SARS and MERS, and now, a new variant has been identified in 2019 which is the novel coronavirus disease 2019. The novel coronavirus disease 2019 (COVID-19) first appeared in Wuhan, China, and quickly spread throughout the world. Their incident rate is high in winter or in moderate temperature. Clinically, we identified the virus presence by PCR-based test. Preventive measures and vaccination are the only treatment against coronavirus. Some of them are remdesivir (GS-5734), chloroquine, hydroxychloroquine, theaflavin, ritonavir, and arbidol. A topological index (TI) is a mathematical function that assigns a numerical value to a (molecular) graph and predicts many physical, chemical, biological, thermodynamical, and structural features of that network. In this work, we will calculate a new topological index namely, atom-bond connectivity (ABC) index, Geometrically Arithmetic (GA) index, Sombor index, Multiplicative Sambor index, and its reduced version for the molecular graph of remdesivir (GS-5734), chloroquine, hydroxychloroquine, theaflavin, ritonavir, and arbidol. We also plot our computed results to examine how they were affected by the parameters involved. The results obtained can aid in the design of new medicine for the treatment of COVID-19.